2023
DOI: 10.1186/s13756-023-01287-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vancomycin-resistant Enterococci in India between 2000 and 2022: a systematic review and meta-analysis

Emily Smout,
Navaneethan Palanisamy,
Sabeel P Valappil

Abstract: Background Vancomycin-resistant Enterococci (VRE) infections are recurrently reported in different parts of India in the last two decades. However, an up-to-date, countrywide information concerning the prevalence and the rate of VRE in India is limited and hence this study aimed to estimate the pooled prevalence of VRE in India. Methods A literature search was performed using various databases. The Preferred Reporting Items for Systematic Reviews a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…The most common species isolated in this study was E. faecalis (n = 120, 60%) followed by E. faecium (n = 55, 27.5%) while other species account for only 12.5% of strains isolated. This is in agreement with many previous studies [8,15]. E. faecalis is the most common species of this genus (80-90%), causing clinical infections, while E. faecium accounts for a very low percentage (5-15%) [16].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The most common species isolated in this study was E. faecalis (n = 120, 60%) followed by E. faecium (n = 55, 27.5%) while other species account for only 12.5% of strains isolated. This is in agreement with many previous studies [8,15]. E. faecalis is the most common species of this genus (80-90%), causing clinical infections, while E. faecium accounts for a very low percentage (5-15%) [16].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of vancomycin resistant Enterococci (VRE) is increasing worldwide [7]. Studies from India show a widespread variation in the prevalence of VRE, ranging from 0-30% with an overall prevalence of 12.4%, and studies have shown a steady increase from 4.8% in 2010 to 14.1% in 2020 [8]. Enterococci are known reservoirs of antibiotic resistance genes and effectively transfer them to different bacteria, like methicillin resistant Staphylococcus aureus [9].…”
mentioning
confidence: 99%
“…However, in this study, all Enterococcus strains were sensitive to linezolid and vancomycin, which is discordant with our study. This difference could be due to the emerging resistance to second-line drugs [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 In India, based on 19 selected studies, the pooled prevalence of VRE was estimated at 12.4% (95% CI 8.6–17.5). 6 In Africa, an overall pooled prevalence of VRE was 26.8% (95% CI 10.7–43.0%) with a one-health perspective. 7 In Ethiopia, different prevalence studies among different study populations and clinical specimens reported 6.7–22.7% VRE.…”
Section: Introductionmentioning
confidence: 98%